Hukum Jual Beli Kucing Hias di Toko Loly Petshop Jalan Suromenggolo Ponorogo - Nurul Ihtiawati Baroroh (Rechtsvinding, 2023)
This study discusses muamalah activities regarding the buying and selling of ornamental cats carried out by the Ponorogo community without considering the law and also regarding the expensive price of cats with unclear benefits or whether these cats are not necessarily beneficial to their owners. So this research will discuss how the legal analysis of the sale and purchase contract of decorative cats at the Loly Petshop shop on Jalan Suromenggolo Ponorogo and how to analyze the maslahah of the object of buying and selling cats at the Loly Petshop shop on Jalan Suromenggolo Ponorogo. This research is a field research with qualitative methods. Researchers conduct research in the field directly to find facts and phenomena that occur in the field. This research data collection technique using observation and interview techniques. The results of this study are that in the case of buying and selling of ornamental cats, it is permissible (mubah), the requirements for goods that are lawful to be sold, provide benefits and can also be known for the goods, the goods being traded are sacred goods. Thus, trading unclean goods is not justified even though cats usually sleep or walk carelessly, but cats are sacred animals. According to the maslahah study, there are two opinions, the first assumes that cats can be used as a business field, that is, they can be resold when the cats have given birth because ornamental cats have a high value, so that it can be said to be tahsiniyah needs. The second opinion says that cats are entertainment, reduce stress and playmates, but for people with middle to upper economic levels, cats are included in the needs of hajiyat. So the cat here includes the scope of hajiyat and tahsiniyat, namely things that complete the needs of dharuriyat.